2014
DOI: 10.1186/1756-3305-7-359
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics and habitat preferences of Phlebotomus orientalis in extra-domestic habitats of Kafta Humera lowlands – kala azar endemic areas in Northwest Ethiopia

Abstract: BackgroundKafta Humera lowlands are endemic for kala-azar (visceral leishmaniasis). These lowlands are characterized by black clay soil which is used for growing sesame, sorghum and cotton for commercial purposes.The aim of this study was to determine seasonal dynamics and habitat preferences of Phlebotomus orientalis, the vector of kala-azar, in extra-domestic habitats of Kafta Humera lowlands.MethodsCDC-light Trap [CDC-LT] and Sticky paper Trap [ST] were used to collect sand flies from different habitats bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 21 publications
12
34
1
Order By: Relevance
“…orientalis collected by STs in both districts showed that farm field was the most productive habitat than that of mixed forest and indoor habitats. Similar findings have been observed by Lemma et al [14] in Kafta-Humera district, north of Metema district. In both areas, majority of the farm field consists of black-cotton soil.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…orientalis collected by STs in both districts showed that farm field was the most productive habitat than that of mixed forest and indoor habitats. Similar findings have been observed by Lemma et al [14] in Kafta-Humera district, north of Metema district. In both areas, majority of the farm field consists of black-cotton soil.…”
Section: Discussionsupporting
confidence: 91%
“…Dry season occurrence and abundance of P . orientalis has previously also noted by several investigators in Sudan [12, 13] and in Ethiopia [14, 28], although peak months of abundance may vary with locality and method of collection. Thus, in the highland area, P .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Of the entire current VL incidence reported, about 90% cases are from seven countries (Brazil, Ethiopia, India, Kenya, Somalia, South Sudan and Sudan). Similarly, the majority of CL cases are endemic in only ten countries (Afghanistan, Algeria, Brazil, Colombia, Ethiopia, Iran, Pakistan, Peru, Saudi Arabia and Syria) (Desjeux, 2004;Murray et al, 2005;Lemma et al, 2014;WHO, 2014;Hailu et al, 2016, Lemma, 2018. Eastern Africa is the second largest VL foci after the Indian subcontinent, contributes to the global burden with 30,000-40,000 new cases per year (Leta et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In village habitats, the vector rarely enters inside the huts/rooms but can be quite abundant in the courtyards of the houses (outdoor site) or in the peri-domestic habitats [6,7]. In Sudan, Ethiopia and the Republic of South Sudan, P. orientalis shows marked seasonality, reaching peak abundance at late dry season (March-June) and disappearing during the months of heavy rains (August -September) [6][7][8][9].…”
mentioning
confidence: 99%